Índice Biótico e Índice de Polución del río Qochoq - Calca, Cusco - Gil Mora, Juan Eduardo (2023)
The Qochoq river originates in the aquarium divortium, from the Amparaes pass at 5 650 masl, and in the snowmelt of the Ccolque Cruz, which are part of the eastern mountain range in the Calca province, Cusco; it has a runoff area of ​​162.85 km2 and a length of 20.81 km, flowing into the city of Calca in the Vilcanota river at 2 929 m of altitude. Throughout its journey it receives tributaries and due to the various economic activities such as livestock in the upper part, agricultural in the intermediate and lower zone, as well as the discharge of wastewater, solid waste and others, it loses its quality for various uses. For the determination of the water quality, the biotic indices and pollution indices were used, applying the methodology proposed by Tuffery & Verneaux using systematic lists based on macroinvertebrates or bioindicators for the determination of the biotic indices and pollution indices; The results indicate that the Qochoq river has lost its quality, it starts with a biotic index of eight for sampling station one with an acceptable water quality due to its clear and oxygenated waters; on the other hand, the pollution index in sampling station one is two and culminates with a pollution index of eight, meaning that the river along its route has lost its quality and showing that pollution is very important and quality of water is dangerous.